Chronic health conditions related to quality of life for federal civil servants - Luciana Eduardo Fernandes Saraiva; Lays Pinheiro de Medeiros; Marjorie Dantas Medeiros Melo; Manuela Pinto Tiburcio; Isabelle Katherinne Fernandes Costa; Gilson de Vasconcelos Torres
OBJECTIVE: The aim of this study is to correlate the QOL domains of the civil servants to the type and number of chronic health conditions. METHOD: A transversal, quantitative study, conducted at the Department of Civil Servant Assistance of the Federal University of Rio Grande do Norte with 215 civil servants, during the period from March to May 2011. RESULTS: Among the chronic health conditions studied, there was significant relationship between non-communicable chronic disease and QOL scores, correlating weakly (r <-376; p <0.008) in the other fields. It was found that the greater the number of chronic conditions, the lower the values on the QOL scale. CONCLUSION: The quality of life of civil servants is negatively influenced by chronic health conditions, compromising, in general, their daily work and life activities.